2017
DOI: 10.1007/s13197-016-2485-4
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, chemical characterization and antioxidant activity of Litchi chinensis Sonn. and Avena sativa L. seeds extracts obtained from pressurized n-butane

Abstract: The extraction of litchi (Litchi chinensis Sonn.) and oat (Avena sativa L.) seeds were investigated using nbutane as pressurized solvent by evaluating the effect of pressure in the range of 7-100 bar and temperature from 25 to 70°C on the extract yield and chemical composition together with the antioxidant activity of the extracts obtained. It was experimentally observed extraction yields for both seeds up to *3.5 wt%, with a total phenolic content around 126.4 mg GAE/100 g of extract, and an antioxidant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The results revealed that the phytochemicals of litchi seed act as a strong antioxidant identical to ascorbic acid (Table 6). Paliga et al, 2017 andShukla et al, 2013 reported the antioxidant activity of litchi seed phytochemicals higher than 78.36%. Ibrahim and Mohamed, (2015) reviewed the chemical constituents and pharmacological activities of litchi seed, listing the single constituents known over the past few decades.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the phytochemicals of litchi seed act as a strong antioxidant identical to ascorbic acid (Table 6). Paliga et al, 2017 andShukla et al, 2013 reported the antioxidant activity of litchi seed phytochemicals higher than 78.36%. Ibrahim and Mohamed, (2015) reviewed the chemical constituents and pharmacological activities of litchi seed, listing the single constituents known over the past few decades.…”
Section: Discussionmentioning
confidence: 99%
“…He also found that EPC in the LS was 89.5 mg GAE/g extract and LS inhibited the DPPH radical with an IC 50 value of 0.65 mg/mL, demonstrating concentration-dependent antiradical action. However, Paliga et al [27] found that the EY of LS was around 3.5 wt%, total phenolic content of about 126.4 mg GAE/100 g and AOA of up to 78.36%. Similarly, Prasad et al [44] observed that maximum EY was found at 50% ethanol extract (26.8%), whereas 100% ethanol only produced 23.3%.…”
Section: Optimization Of Extraction Of Phenolic Compounds Using Rsmmentioning
confidence: 95%
“…Conventional and microwave extraction methods were used with different solvent such as distilled water, ethanol, citric acid, and baking soda. Paliga et al [27] investigated the effect of pressurized solvent (n-butane) on the extraction yield (EY), chemical composition and antioxidant activity (AOA) of LS extract using 7-100 bar and temperature in the range of 25 • C to 70 • C. Type and concentration of solvent, extraction temperature and time, solid-to-liquid ration, pressure, and pH may strongly affect the extraction process. It is necessary to optimize the extraction process before extraction of phenolic compounds [28].…”
Section: Introductionmentioning
confidence: 99%
“…In China, the seed of Litchi chinensis as TCMs is prescribed in many formulas for a long time owing to its great medicinal value [338]. The chemical studies show that the components in the seed of Litchi chinensis mainly are polyphenols, such as rutin, gallic acid, procyanidin B2, gallocatechin, epicatechin, and epicatechin-3-gallate [339]. In our research group, a purified active fraction named lychee seed fraction enriching polyphenol (LSP) is obtained from lychee seed and its neuroprotective effect is investigated in multiple models of AD [340].…”
Section: Litchi Chinensismentioning
confidence: 99%